Sikap Petani terhadap Program Perluasan Area Tanam (PAT) di Kecamatan Weru Kabupaten Cirebon - Defi Febriyanti; Sugihardjo Sugihardjo; Eksa Rusdiyana (Universitas Sebelas Maret, 2025)
The Planting Area Expansion (PAT) program aims to optimize rice fields that were previously hampered by water limitations through the use of water pumps to increase water availability during the dry season. The objectives of the study were to analyze farmers’ attitudes towards the PAT program, describe factors that shape these attitudes, and examine the relationship between these factors and farmers’ attitudes in Weru Sub-district, Cirebon Regency. The method used was quantitative with data collection through observation, interviews using questionnaires, and documentation. A total of 77 farmers were determined as respondents using the proportional random sampling technique, and the data were analyzed using the Spearman rank correlation test. The results showed that most farmers were hesitant regarding the outcomes and impacts of the PAT program due to increased production costs during the dry season, leading them to disagree with its benefits. The farming experience factor had a significant positive relationship with farmers’ attitudes, while formal education, non-formal education, and the role of people considered important had a significant negative relationship. Age and local culture factors did not have a significant relationship with farmers’ attitudes. These results indicate that farming experience contributes to forming a more positive attitude towards the PAT program, while education, intensity of extension, and social roles tend to form attitudes that are hesitant or less supportive. This study suggests that experienced farmers be the main target of the program and reduce the intensity of discussions about the PAT program in agricultural extension activities.